The new services in nagios network bandwidth utility email notification and sms alert in improving the network performance - Mohammad Ali Arsyad, Mohd Shuhaimi; Irda , Roslan; Zaheera, Zainal Abidin; Mohd Zaki, Mas'ud; Syarulnaziah, Anawar (2011)
A new feature of services in Nagios has been added to the existing system which has no such services. The bandwidth monitoring and notification system are configured for alerting the network administrators when the bandwidth of the network in an organization hits a certain threshold settings. The system sent an email alert and sms notification to the network administrator for taking further action in order to maintain the Quality of Service (QoS) in the network. All the logs file of the Nagios actions is saved in the Nagios File Logs. The analysis was conducted from the case study and problem statements. Network Development Life Cycle (NDLC) was chosen as a methodology for implementing this system in the network. Nagios is installed inside Ubuntu 10 Operating System along with Multi-Router Traffic Grapher (MRTG) and Mail Postfix. MRTG and Mail Postfix were configured to be integrated with the Nagios System. On the client side, NSClient++ has been installed, for monitoring the bandwidth and performance of windows based on operating system. The Nagios services have been improved with the implementation of sms and emails notifications since the existing services have no such utilities. With the implementation of these services to Nagios, the performance could be even better for the future